TOPICAL CORTICOSTEROIDS IN ORAL PATHOLOGY - Adriana Krasteva; Assya Krasteva; Angelina Kisselova-Yaneva (Peytchinski Publishing, 2010)
Topical corticosteroids have been commonly used over the last 50 years to treat various inflammatory mucosal conditions. The wide spectrum of potencies and bases allows these medications to be used effectively and safely under the care of an experienced dental practitioner.